Redundancy of human ATG4 protease isoforms in autophagy and LC3/GABARAP processing revealed in cells. Issue 6 (3rd June 2019) - Agrotis, Alexander; Pengo, Niccolo; Burden, Jemima J.; Ketteler, Robin
ABSTRACT: Macroautophagy/autophagy is a cellular degradation pathway that delivers cytoplasmic material to lysosomes via double-membrane organelles called autophagosomes. Lipidation of ubiquitin-like LC3/GABARAP proteins on the autophagosome membrane is important for autophagy. The cysteine protease ATG4 executes 2 LC3/GABARAP processing events: priming of newly synthesized pro-LC3/GABARAP to enable subsequent lipidation, and delipidation/deconjugation of lipidated LC3/GABARAP (the exact purpose of which is unclear in mammals). Four ATG4 isoforms (ATG4A to ATG4D) exist in mammals; however, the functional redundancy of these proteins in cells is poorly understood. Here we show that human HAP1 and HeLa cells lacking ATG4B exhibit a severe but incomplete defect in LC3/GABARAP processing and autophagy. By further genetic depletion of ATG4 isoforms using CRISPR-Cas9 and siRNA we uncover that ATG4A, ATG4C and ATGD all contribute to residual priming activity, which is sufficient to enable lipidation of endogenous GABARAPL1 on autophagic structures. We also demonstrate that expressing high levels of pre-primed LC3B in ATG4-deficient cells can rescue a defect in autophagic degradation of the cargo receptor SQSTM1/p62, suggesting that delipidation by human ATG4 is not essential for autophagosome formation and fusion with lysosomes. Overall, our study provides a comprehensive characterization of ATG4 isoform function during autophagy in human cells. Abbreviations: Atg: autophagy-related; baf A1: bafilomycin A1; CASP3: caspase 3; CLEM: correlative light and electron microscopy; CMV: cytomegalovirus; CRISPR: clustered regularly interspaced short palindromic repeats; DKO: double knockout; EGFP: enhanced green fluorescent protein; GABARAP: GABA type A receptor-associated protein; GABARAPL1: GABA type A receptor-associated protein like 1; GABARAPL2: GABA type A receptor-associated protein like 2; GFP: green fluorescent protein; HB: homogenization buffer; KO: knockout; LAMP1: lysosomal associated membrane protein 1; LIR: LC3 interacting region; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MFN2: mitofusin 2; N.A.: numerical aperture; NEM: N-ethylmaleimide; PDHA1: pyruvate dehydrogenase E1 alpha 1 subunit; PLD: phospholipase D; PE: phosphatidylethanolamine; RLUC: Renilla luciferase; SQSTM1: sequestosome 1; TEM: transmission electron microscopy; TKO: triple knockout; ULK1: unc-51 like autophagy activating kinase 1; VCL: vinculin; WT: wild-type